The Role of Generation Z Teachers in Learning Religious and Moral Values for Early Childhood Education in Selebar District, Bengkulu City - Suriyanti Suriyanti; Nelly Marhayati; Alimni Alimni (TANJAK, 2026)
The development of digital technology has transformed the characteristics of educators, including the emergence of Generation Z teachers who demonstrate high adaptability to information technology in the learning process. These characteristics provide both opportunities and challenges in early childhood religious and moral values education, which emphasizes role modeling, habituation, and character development. This study aims to analyze the role of Generation Z teachers in teaching religious and moral values to early childhood learners, identify the challenges encountered, and describe the strategies implemented in digital era learning at kindergartens in Selebar District, Bengkulu City. This study employed a qualitative approach using a case study design. The participants consisted of six informants, including three Generation Z teachers and three principals from three kindergartens in Selebar District, Bengkulu City. Data were collected through observation, in depth interviews, and documentation studies, and analyzed using the Miles, Huberman, and Saldaña model through data condensation, data display, and conclusion drawing and verification. The findings reveal that Generation Z teachers perform roles as role models, facilitators, motivators, mentors, innovators, and evaluators in religious and moral values learning. The implementation of religious and moral education is carried out through religious habituation, exemplary practices, storytelling, educational play activities, and selective use of digital media. The study also identifies challenges related to children’s gadget use, limited parental involvement, pedagogical experience, and the balance between technology utilization and character formation. The findings confirm that Generation Z teachers have significant potential to provide adaptive religious and moral values education while maintaining the essence of character development.